Emotional abuse and its relationship to self- confidence among middle school teachers - Al-Saadi, Ayad Hashem Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to identify • Emotional abuse for middle school • Self-confidence among middle school • The significance of the statistical differences in the relationship between emotional abuse and self-confidence according to the gender variable (male, female). • The direction and strength of the relationship between emotional abuse and self-confidence among middle school To achieve the goals of the research, the researcher built a measure of emotional abuse according to Claser’s theory (Glasser, 2000), and adopted a measure of self-confidence for (Maneh, 2015), and applied the two measures to the research sample, which consisted of (400) teachers and schools (married) from the Baquba District Center After they were chosen by the stratified random method, the number of male and female teachers was determined proportionally. After statistically treating the study data using (T-test for one sample, and T-test for two independent samples, Pearson correlation coefficient, Alpha Cronbach equation, and Z-test), the research reached the following results: The members of the research sample do not have emotional abuse, that the members of the research sample have Self-confidence level is high compared to the theoretical average of the scale, there are no statistically significant differences in the correlative relationship between emotional abuse and self-confidence according to the gender variable (male - female), there is no statistically significant relationship between emotional abuse and self- confidence, and in the light of these results the research has come out With a set of recommendations and suggestions.